Sensitivity of boundary layer schemes in simulating the asymmetric rainfall of landfalling typhoon Lekima (2019) - Duan, Jingjing; Yu, Zifeng; Hu, Bo; Zhen, Yan; Cheung, Kevin K. W.; Li, Yubin; Cai, Zhiying (Frontiers in Earth Science, 2022)
A group of control (CTL) plus ten sensitivity numerical experiments have been conducted to investigate the sensitivity of planetary boundary layer (PBL) schemes in simulating the asymmetric precipitation distribution of typhoon Lekima (2019) during landfall. The simulated track and intensity are quite sensitive to the choice of PBL scheme. In the CTL that applies the Mellor-Yamada Nakanishi and Niino (MYNN) PBL and surface layer scheme, the observed eyewall replacement 6 h prior to landfall as well as the asymmetric precipitation during landfall has been simulated well. However, in the PBL1 experiment that applies the Yonsei University (YSU) PBL scheme and the Revised Mesoscale Model version 5 (MM5) Monin-Obukhov surface layer scheme, no double eyewall is simulated. PBL1 and the other sensitivity experiments also simulate more axisymmetric precipitation distribution. The PBL1 simulates intensification just before landfall, sustains intensity longer after landfall, but then dissipates quite rapidly. Such differences from the CTL are due to larger enthalpy flux, higher PBL height (which almost unchanged in the CTL) and with eddy diffusivity extending more into the free atmosphere in the PBL1. These factors lead to outward expansion of the radius of maximum wind, larger radial inflow, larger axisymmetric tangential wind in the boundary layer and larger updraft in the eyewall. After landfall, larger momentum flux and larger friction velocity in the PBL1 enables the more rapid dissipation. The intensification before landfall in PBL1 make the axisymmetric component stronger. Asymmetry developed in the outer eyewall, PBL1 was less successful in simulating the eyewall replacement that affect the degree of rainfall asymmetry. These results indicate that the model PBL schemes largely influence the simulated tropical cyclone (TC) intensity and structure including asymmetric rainfall distribution during landfall.